A national survey on radiation oncology patterns of practice in Switzerland during the COVID-19 pandemic: Present changes and future perspectives. (September 2020) - Achard, Vérane; Aebersold, Daniel M.; Allal, Abdelkarim S.; Andratschke, Nicolaus; Baumert, Brigitta G.; Beer, Karl T.; Betz, Michael; Breuneval, Thomas; Bodis, Stephan; de Bari, Berardino; Förster, Robert; Franzetti-Pellanda, Alessandra; et al.
Highlights: We conducted a Swiss survey on patterns of practice during COVID-19 pandemic. Dedicated IT solutions were implemented in all radiation-oncology departments. Upfront endocrine treatments for breast and prostate cancer were privileged. Use of hypofractionation for breast, rectal cancer and palliation was increased.